INTERNALISASI JIWA WIRAUSAHA SISWA MA AL-ITTIHAD MELALUI PENDIDIKAN KEWIRAUSAHAAN - Khoirun Nisa; Yhadi Firdiansyah; Saiful Amin; Ali Nasith (Program Studi Pendidikan Ilmu Pengetahuan Sosial, Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The objectives of this study are to: (1) describe the planning of learning programs to instill the entrepreneurial spirit of students through entrepreneurship education. (2) Describe how the implementation of learning to instill the entrepreneurial spirit of students through entrepreneurship education. (3) Describe the obstacles and solutions in the internalization process to instill the entrepreneurial spirit of students through entrepreneurship education. This research uses a qualitative approach with the type of case study research. Data collection techniques used structured and unstructured interviews, participant observation, and photo documentation of activities. Meanwhile, for data analysis using Miles and Huberman interactive techniques, namely data collection, data condensation, data presentation, and drawing conclusions/verification. Meanwhile, the data validity test was in the form of a research data credibility test. The results of research conducted by researchers show that: (1) Entrepreneurship learning planning at MA Al-Ittihad always carries out needs analysis (needs analysis),a) preparing students, b) learning (curriculum, number of hours, evaluations, and products), c) and learning practices. (2) The implementation of entrepreneurship learning at MA Al-Ittihad is not only learning material in class and practical in the laboratory, but also activities such as bazaars, street vendors for class XI, and workshops on entrepreneurship. (3) Obstacles in learning entrepreneurship at MA Al-Ittihad such as the mindset of students who are less developed and their lack of creativity, very limited allocation of study time, and inadequate infrastructure. The solutions that are carried out by the school and teachers such as providing motivation to students and improving infrastructure that are less supportive in the learning process. Abstrak Tujuan penelitian ini adalah untuk: (1) mendeskripsikan perencanaan program pembelajaran untuk menanamkan jiwa kewirausahaan siswa melalui pendidikan kewirausahaan. (2) Mendeskripsikan bagaimana pelaksanaan pembelajaran menanamkan jiwa kewirausahaan siswa melalui pendidikan kewirausahaan. (3) Mendeskripsikan kendala dan solusi dalam proses internalisasi untuk menanamkan jiwa kewirausahaan siswa melalui pendidikan kewirausahaan. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data menggunakan wawancara terstruktur dan tidak terstruktur, observasi partisipan, dan dokumentasi foto kegiatan. Sedangkan untuk analisis data menggunakan teknik interaktif Miles dan Huberman yaitu pengumpulan data, kondensasi data, penyajian data, dan penarikan kesimpulan/verifikasi. Sedangkan uji validitas data berupa uji kredibilitas data penelitian. Hasil penelitian yang dilakukan peneliti menunjukkan bahwa: (1) Perencanaan pembelajaran kewirausahaan di MA Al-Ittihad selalu melakukan analisis kebutuhan (needs analysis), a) mempersiapkan siswa, b) pembelajaran (kurikulum, jumlah jam, evaluasi, dan produk). (c) dan praktik pembelajaran. (2) Pelaksanaan pembelajaran kewirausahaan di MA Al-Ittihad tidak hanya materi pembelajaran di kelas dan praktik di laboratorium, tetapi juga kegiatan seperti bazar, pedagang kaki lima untuk kelas XI, dan workshop kewirausahaan. (3) Hambatan dalam pembelajaran kewirausahaan di MA Al-Ittihad seperti pola pikir siswa yang kurang berkembang dan kreativitasnya yang kurang, alokasi waktu belajar yang sangat terbatas, dan sarana prasarana yang kurang memadai. Solusi yang dilakukan pihak sekolah dan guru seperti memberikan motivasi kepada siswa dan memperbaiki sarana prasarana yang kurang mendukung dalam proses pembelajaran.